2013
DOI: 10.1177/0954410013515381
|View full text |Cite
|
Sign up to set email alerts
|

Application of conjugate heat transfer and fluid network analysis to improvement design of turbine blade with integrated cooling structures

Abstract: A combination of fluid network analysis method with conjugate heat transfer are applied to the improvement design of the integrated cooling structures in a high-performance turbine blade, coupled with the 3D viscous solver for the gas flow field. By comparison with the experimental results of open literatures, the methodology developed is numerically validated. For a high-pressure turbine rotor blade, it is used to rapidly predict and evaluate the aerodynamic and heat transfer performances of its integrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Here, the momentum, continuity, and energy equations are resolved along with the turbulence equations for modeling the turbulence quantities. Most of the previous researchers 14 had successfully used the shear stress transport (SST) model over Reynolds averaged navier-stokes model for predicting heat transfer on a turbine airfoil. For pressure velocity coupling, SIMPLE algorithm is used.…”
Section: Modeling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the momentum, continuity, and energy equations are resolved along with the turbulence equations for modeling the turbulence quantities. Most of the previous researchers 14 had successfully used the shear stress transport (SST) model over Reynolds averaged navier-stokes model for predicting heat transfer on a turbine airfoil. For pressure velocity coupling, SIMPLE algorithm is used.…”
Section: Modeling Methodologymentioning
confidence: 99%
“…This was attributed to the particular placement of film holes and outlets of the cooling flows. Peigang et al 14 reported a conjugate heat transfer study using integrated cooling systems in a high-performance turbine blade and suggested three ways for the improved design namely: (i) increasing coolant flow ratio, (ii) improving the turning of serpentine channels to minimize the resistance of inner coolant flow, and (iii) adjustment of the local cooling structure dimension according to the high-temperature region on the outer surface of the blade.…”
Section: Introductionmentioning
confidence: 99%